2020
DOI: 10.1101/2020.11.23.394197
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Endogenous p53 expression in human and mouse is not regulated by its 3′UTR

Abstract: Inactivation of p53 occurs in many cancers. microRNAs and RNA-binding proteins are thought to repress p53 expression through its 3’ untranslated region (3’UTR), thus contributing to tumorigenesis. We used CRISPR/Cas9 to delete the human and mouse p53 3’UTRs while preserving endogenous mRNA processing. This revealed that the endogenous 3’UTR is not involved in the regulation of p53 mRNA or protein expression, neither in steady state nor after genotoxic stress.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…The two TP53 constructs produced similar induced levels of p53 protein (Fig. 1a), indicating that the 3’UTR does not appreciably affect p53 expression, consistent with a recent report 21 . As expected, TP53 CR induction substantially reduced cell proliferation.…”
Section: Resultssupporting
confidence: 91%
“…The two TP53 constructs produced similar induced levels of p53 protein (Fig. 1a), indicating that the 3’UTR does not appreciably affect p53 expression, consistent with a recent report 21 . As expected, TP53 CR induction substantially reduced cell proliferation.…”
Section: Resultssupporting
confidence: 91%
“…Similarly, p53 contains a natural antisense transcript, designated Wrap53, that regulates endogenous p53 mRNA levels and further induction of p53 protein by targeting the 5′ untranslated region of p53 mRNA (64). Finally, the 3’ UTR of p53 is the target of many different microRNAs, lncRNAs and RNA-binding proteins that could influence mRNA stability (61,65); however the extent to which the 3’ UTR influences Trp53 mRNA half-life has recently been brought into question (66). Nevertheless, differential expression of factors that post-transcriptionally influence p53 mRNA levels in Lmna KO skeletal muscle could be contributing to the increased p53 mRNA levels observed in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…However, alterations in alternative 3′UTR isoform expression often do not change overall protein levels (Fig. 1) 12,14,20,84,85 . For those cases, it has been demonstrated that isoform-specific differences in protein localization or function occur through 3′UTR-mediated formation of alternative protein complexes [11][12][13][14][15] .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, malignant B cells preferentially form long 3′UTRdependent protein complexes that have tumor-promoting roles 12 . So far, most studies that investigated the functional consequences of alternative 3′UTR isoform expression have relied on using expression constructs, but more recently CRISPR-mediated deletions of 3′UTRs were added to the tool kit [11][12][13][14][15]25,[84][85][86] . Alternatively, as we showed here, 3′UTR isoform expression can be altered through enhancer deletion (Fig.…”
Section: Discussionmentioning
confidence: 99%